Job Embeddedness sebagai Variabel Mediasi Pengaruh Leader Member Exchange dan Perceived Organizational Support terhadap Job Insecurity Karyawan di Beberapa Bank Syariah - Zakiy, Muhammad; Aeni, Farikha (Universitas Islam Negeri Sunan Kudus, 2022)
The adaptability of the relationship between leader-member and organizational support effect of job insecurity that appears in employees. This adaptability can be seen from the influence of leader-member exchange and perceived organizational support which can lead to job insecurity. This study aims to examine the effect of leader-member exchange and perceived organizational support on job insecurity with job embeddedness as an intervening variable. The objects of this research are 3 syariah banking such as Bank Syariah Indonesia, Bank Muamalat and Bank Madina Syariah. This research is quantitative. The sample used in this study was 257 respondents obtained by the non-probability sampling method. Data were collected using a questionnaire, analyzed using SmartPLS version 3.2.8. The results of this study indicate that there is a positive influence between leader-member exchange on job embeddedness, perceived organizational support has a positive effect on job embeddedness, job embeddedness has no effect on job insecurity, the leader-member exchange has no effect on job insecurity, and perceived organizational support has a negative effect on job insecurity.